2017
DOI: 10.1108/mrr-03-2016-0058
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the causal link between a management improvement technique and organizational performance

Abstract: Purpose An important question in contemporary research is: do certain management practices cause better performance or do better performing organizations find it easier to adopt certain management practices? This question is also of importance when applying the high performance organization (HPO) framework, which is a scientifically validated technique designed to achieve and sustain a high level of performance. Many research studies correlate the HPO framework with improved organizational performance. There a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 41 publications
(54 reference statements)
2
33
0
Order By: Relevance
“…This inference mirrors earlier findings from de Waal & Goedegebuure (2017), who similarly observed, in a comparison of two units in one company undergoing an HPO transition, that one unit achieved a higher HPO score and organizational results while the other attained a lower HPO score and organizational results. The reason for those dissimilar results turned out, likewise, to be related to the seriousness with which the management team of the respective units applied the HPO Framework.…”
Section: Role Of Management During the Hpo Transitionsupporting
confidence: 77%
See 1 more Smart Citation
“…This inference mirrors earlier findings from de Waal & Goedegebuure (2017), who similarly observed, in a comparison of two units in one company undergoing an HPO transition, that one unit achieved a higher HPO score and organizational results while the other attained a lower HPO score and organizational results. The reason for those dissimilar results turned out, likewise, to be related to the seriousness with which the management team of the respective units applied the HPO Framework.…”
Section: Role Of Management During the Hpo Transitionsupporting
confidence: 77%
“…This last research question is of interest as recent research (de Waal & Goedegebuure, 2017) has found that managerial involvement is crucial for a successful implementation of the HPO Framework. The theoretical contribution of the present study is that it will extend and enhance existing research about the achievement of high performance in the African organizational context, specifically in the governmental sector, a topic that has not received much academic attention to date.…”
Section: Introductionmentioning
confidence: 99%
“…The study results showed that the effects of the HPO Framework were different depending on local circumstances. Some of the locations experienced a growth in sales because of applying the HPO Framework, something that was expected on the basis of previous HPO research ( de Waal, 2012;de Waal & Goedegebuure, 2017). At the same time, other locations used the HPO Framework to battle the consequences of the adverse economic circumstances they found themselves in.…”
Section: Conclusion Limitations and Future Researchmentioning
confidence: 79%
“…Average scores indicate points where the organization has to take action in order to become an HPO. Since the development of the HPO framework, multiple longitudinal studies have been performed that show the positive correlation between the HPO scores of an organization and its performance [37][38][39][40][41]. In these studies, organizations that worked with discipline and dedication and thus increased their HPO scores all experienced increased organizational performance.…”
Section: The Hpo Frameworkmentioning
confidence: 99%